2017
DOI: 10.15448/1983-652x.2017.2.24244
|View full text |Cite
|
Sign up to set email alerts
|

Inflamação e associação com parâmetros clínicos e nutricionais de pacientes em hemodiálise

Abstract: Exceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons BY-NC 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…This influence of age on the malnutrition outcome is associated with several factors, but especially those related to the reduction of lean mass and muscle strength resulting from the various metabolic, hormonal and nutritional disorders of CKD, contributing to the increasingly prevalent sarcopenia in the elderly population. ( 22 ) In their study, Sampaio et al, ( 32 ) reported that the increase in age reflected the increase in MIS. Qureshi et al, ( 33 ) reported that elderly patients were often more malnourished than younger ones, according to the ASG, in addition to having lower HGS, similar to this study.…”
Section: Discussionmentioning
confidence: 92%
“…This influence of age on the malnutrition outcome is associated with several factors, but especially those related to the reduction of lean mass and muscle strength resulting from the various metabolic, hormonal and nutritional disorders of CKD, contributing to the increasingly prevalent sarcopenia in the elderly population. ( 22 ) In their study, Sampaio et al, ( 32 ) reported that the increase in age reflected the increase in MIS. Qureshi et al, ( 33 ) reported that elderly patients were often more malnourished than younger ones, according to the ASG, in addition to having lower HGS, similar to this study.…”
Section: Discussionmentioning
confidence: 92%
“…As características socioeconômicas e demográficas dos participantes avaliados no atual estudo foram semelhantes àquelas encontradas em outros estudos nacionais em que a maioria dos pacientes com DRC é do sexo masculino (18,19) , de raça/cor parda (18,19) , que vivem com companheiro(a) (20) , com baixo nível socioeconômico (19,20) e de escolaridade (18,19) . Quanto às etiologias presuntivas mais frequentes de DRC, verificou-se que a nefroesclerose hipertensiva e a nefropatia diabética, juntas, somaram mais da metade dos casos encontrados.…”
Section: Discussionunclassified
“…No presente estudo, os participantes com pontuação igual ou maior que seis pontos no MIS foram classificados com pior condição nutricional. A pontuação média observada para o MIS foi semelhante aos valores encontrados em outros estudos realizados com pacientes renais crônicos pelo mundo (18,23) .…”
Section: Discussionunclassified